2020
DOI: 10.1371/journal.pmed.1003321
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities associated with mortality in 31,461 adults with COVID-19 in the United States: A federated electronic medical record analysis

Abstract: Background At the beginning of June 2020, there were nearly 7 million reported cases of coronavirus disease 2019 (COVID-19) worldwide and over 400,000 deaths in people with COVID-19. The objective of this study was to determine associations between comorbidities listed in the Charlson comorbidity index and mortality among patients in the United States with COVID-19. Methods and findings A retrospective cohort study of adults with COVID-19 from 24 healthcare organizations in the US was conducted. The study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
399
7
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(463 citation statements)
references
References 18 publications
(32 reference statements)
48
399
7
9
Order By: Relevance
“…and 300%, respectively, compared to those without such comorbidities. These findings were consistent with similar studies elsewhere [4,8,9]. In contrast, similar to a study in the US [8],…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…and 300%, respectively, compared to those without such comorbidities. These findings were consistent with similar studies elsewhere [4,8,9]. In contrast, similar to a study in the US [8],…”
Section: Resultssupporting
confidence: 93%
“…Several other studies in China [26], Brazil [13,27], Uganda [14], and South Africa [15] patients were less frequent in Jakarta (31% of patients) than reported in large patient series in North America [7,8], South America [13], and Europe [9]. This could reflect the relatively young population admitted to Jakarta hospitals, but also under-reporting of comorbidities by patients, or under-diagnosis due to variable access to quality health services.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Age has been reported to be associated with severe disease progression in COVID-19 23 On a different note, patients in the non-SCD group were found to be mostly comorbid with diabetes mellitus (DM) and hypertension (HTN), this could be attributed to the older age of the population 32 . The higher prevalence of DM and HTN increased the baseline risk of the non-SCD group to develop severe COVID-19 outcomes [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…The illness caused by the SARS-CoV-2 virus varies in its symptomatology and can range from being asymptomatic 3 to severe illness leading to acute respiratory distress syndrome and eventually, death 4 . Several studies have shown an association between higher rates of hospitalization and severe illness with advanced age, male gender, heart failure, diabetes mellitus, severe asthma, high body mass index, chronic kidney disease, chronic pulmonary disease and malignancy [5][6][7][8] . Additional factors that are suggestive of more serious COVID-19 complications include admission oxygen saturation of <88%, troponin-I level >1 ng/mL, C-reactive protein level >200 mg/L, and D-dimer levels >2500 ng/mL 6 .…”
Section: Introductionmentioning
confidence: 99%